Про розв'язки на півосі системи лінійних диференціально-функціональних рівнянь з лінійно перетвореним аргументом - Самойленко, А.М.; Денисенко, Н.Л. (Український математичний журнал, 2007)
Получены условия, при которых решениями на полуоси системы линейных дифференциально-функциональных уравнений являются решения некоторой системы обыкновенных дифференциальных уравнений. Conditions are established under which solutions on the semiaxis for a system of linear differentialfunctional equations are determined as solutions of some system of ordinary differential equations.